INTERESTING STORIES ABOUT CHEMICAL ELEMENTS - G‘aniyeva E’zozabonu Rustamjon qizi, Tokhirov Bakhrom Bakhodir o‘g‘li, Oqboyev Khurramjon Odiljon oʻgʻli (Galaxy International Interdisciplinary Research Journal, 2023)
Every society’s future depends on how well-developed its education system is, which is both an essential component and a fundamental requirement. In this article, we can discuss information about some interesting stories about chemical elements.